Rethinking phonons: The issue of disorder. (December 2017) - Seyf, Hamid; Yates, Luke; Bougher, Thomas; Graham, Samuel; Cola, Baratunde; Detchprohm, Theeradetch; Ji, Mi-Hee; Kim, Jeomoh; Dupuis, Russell; Lv, Wei; Henry, Asegun
Abstract Current understanding of phonons treats them as plane waves/quasi-particles of atomic vibration that propagate and scatter. The problem is that conceptually, when any level of disorder is introduced, whether compositional or structural, the character of vibrational modes in solids changes, yet nearly all theoretical treatments continue to assume phonons are still waves. For example, the phonon contributions to alloy thermal conductivity (TC) rely on this assumption and are most often computed from the virtual crystal approximation (VCA). Good agreement is obtained in some cases, but there are many instances where it fails—both quantitatively and qualitatively. Here, we show that the conventional theory and understanding of phonons requires revision, because the critical assumption that all phonons/normal modes resemble plane waves with well-defined velocities is no longer valid when disorder is introduced. Here we show, surprisingly, that the character of phonons changes dramatically within the first few percent of impurity concentration, beyond which phonons more closely resemble the modes found in amorphous materials. We then utilize a different theory that can treat modes with any character and experimentally confirm its new insights. Phonon: correlation rather than scattering In solids, atoms continuously vibrate in collective motions with quantized amplitudes that can be described in terms of quasiparticles known as phonons—which are responsible for heat transfer and sound. Phonons are usually treated as waves that propagate and scatter, but this approach can sometimes fail when dealing with materials with disorder. A team of researchers from the Georgia Institute of Technology, led by Asegun Henry, show that by focussing on phonon correlation rather than scattering, it is possible to more accurately capture the changes in vibrational mode behavior as a function of disorder.